Spiritual needs of family caregivers in palliative care - Uğur Uzun; Serpil Başar; Aykut Saritaş (BMC Palliative Care, 2024)
Abstract Objective The primary aim of this study is to elucidate the spiritual needs encountered by family members who intricately engage in the progression of illness within the palliative care framework, thus assuming the paramount responsibility of caregiving. Methods This study was approved by the Institutional Review Board and Ethics Committee of the University of Health Sciences İzmir Tepecik Training and Research Hospital (17/01/2022–2022/01–16). The research was designed as a prospective study. It was conducted through face-to-face, interactive interviews with family caregivers of patients admitted to the palliative care unit at Tepecik Training and Research Hospital between April 2022 and December 2022. The interviews were performed using a phenomenological approach and structured in a question-and-answer format. Data from twenty family caregivers were analyzed using thematic analysis. The questions were specifically designed to explore the psychological processes, spirituality, conceptions of God, meaning-making, and coping strategies of the family caregivers. Results Caregivers experienced various psychological and emotional states progressing through stages of denial, anger, and acceptance. Spirituality emerged as a critical coping mechanism providing strength and meaning amidst caregiving challenges. Caregivers’ perceptions of God varied from loving to punitive, influencing their interpretations of suffering and caregiving roles. Conclusion This study underscores the importance of integrating spiritual support into palliative care practices. Recognizing and addressing caregivers’ spiritual needs is crucial for enhancing their well-being and improving the quality of palliative care delivery. Training healthcare professionals in spiritual care and implementing targeted interventions can effectively support family caregivers in their caregiving journey.